2021
DOI: 10.1007/s10488-021-01152-4
|View full text |Cite
|
Sign up to set email alerts
|

Online Training of Community Therapists in Observational Coding of Family Therapy Techniques: Reliability and Accuracy

Abstract: A foundational strategy to promote implementation of evidence-based interventions (EBIs) is providing EBI training to therapists. This study tested an online training system in which therapists practiced observational coding of mock video vignettes demonstrating family therapy techniques for adolescent behavior problems. The study compared therapists ratings to gold-standard scores to measure therapist reliability (consistency across vignettes) and accuracy (approximation to gold scores); tested whether reliab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…While our CPS experts were unlikely to gain more knowledge of the approach itself, it appears that training on the coding system, which includes reading and discussing exemplars and receiving feedback on one's ratings of mock sessions, changed the observers’ sensitivity to the nuances of CPS practice beyond what CPS expertise alone could provide. This finding can inform the development of activities to increase practitioners’ fidelity ( Caron & Dozier, 2022 ; Hogue, Porter, et al, 2022 ).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…While our CPS experts were unlikely to gain more knowledge of the approach itself, it appears that training on the coding system, which includes reading and discussing exemplars and receiving feedback on one's ratings of mock sessions, changed the observers’ sensitivity to the nuances of CPS practice beyond what CPS expertise alone could provide. This finding can inform the development of activities to increase practitioners’ fidelity ( Caron & Dozier, 2022 ; Hogue, Porter, et al, 2022 ).…”
Section: Discussionmentioning
confidence: 85%
“…It may also be that providers’ memories of sessions are generally biased or inaccurate. Several methods have been explored to improve the reliability and accuracy of providers’ self-reports, for example, training providers with exemplars, mock ratings of recorded treatment sessions, and fidelity feedback (e.g., Caron & Dozier, 2022 ; Hogue, MacLean, et al, 2022 ; Hogue, Porter, et al, 2022 ). Other ideas include using structured notetaking during sessions or providing abbreviated recordings to increase the recall accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, meaningful conclusions from this trial were not affected by somewhat higher than anticipated ICCs. Like other studies, we relied on self-reported data to measure clinician and beneficiary constructs [ 43 , 44 ]. We took several steps to mitigate this bias, including reminding the clinicians that their responses would not be shared with others and using standardized data collection tools.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly elusive are measurement methods that are both efficient (i.e., feasible) and effective (i.e., rigorously evaluated, psychometrically sound; Schoenwald et al, 2011 ). Observational methods have been a gold standard ( Stirman, 2020 ), but their feasibility in community mental health settings is presumed limited due to resource constraints ( Hogue et al, 2021 ). Until recently, information about fidelity measurement appeared primarily in published treatment efficacy or effectiveness studies and lacked details needed to estimate the associated resource requirements (Schoenwald & Garland, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…However, for clinician self-ratings to be accurate and reliable, training may be required, as the concordance of therapist and observer ratings of EBI components has typically been low ( Caron, et al., 2020 ). In a recent study, an innovative online training system was used to enable community-based therapists to practice observational coding of family therapy techniques in mock video vignettes ( Hogue et al, 2021 ). There were promising training effects on the reliability of therapist ratings—but less so for accuracy—which led the investigators to conclude that stronger training effects would be needed for a meaningful impact on EBI implementation.…”
Section: Introductionmentioning
confidence: 99%